2002
DOI: 10.1002/ijc.10565
|View full text |Cite
|
Sign up to set email alerts
|

Cellular effects of CPT‐11 on colon carcinoma cells: Dependence on p53 and hMLH1 status

Abstract: Irinotecan (CPT-11), a recently introduced component of a standard chemotherapy for colorectal cancer, induces in colon cancer cell lines in vitro cell cycle arrest and apoptosis. Since sporadic colon carcinomas exhibit in 50 -60% mutations in the p53 gene and in 10 -15% an MSI phenotype due in the great majority of the cases to hMLH1 inactivation, we investigated how these lesions influence the cellular effects of CPT-11 by using colorectal carcinoma cell line HCT116 (which has the genotype p53 ؉/؉ ,hMLH1 -) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
58
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 28 publications
23
58
0
Order By: Relevance
“…These results are in agreement with the 'fork collision model' and the S-phase specificity of CPT-11. Therefore, this work reinforces previous reports of higher sensitivity of MMR-deficient cell lines to CPT-11 and offers a potential explanation for it (Jacob et al, 2001;Magrini et al, 2002). Several authors have demonstrated that MSI is a prognostic marker in patients with CRC (Gryfe et al, 2000;Popat et al, 2005).…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…These results are in agreement with the 'fork collision model' and the S-phase specificity of CPT-11. Therefore, this work reinforces previous reports of higher sensitivity of MMR-deficient cell lines to CPT-11 and offers a potential explanation for it (Jacob et al, 2001;Magrini et al, 2002). Several authors have demonstrated that MSI is a prognostic marker in patients with CRC (Gryfe et al, 2000;Popat et al, 2005).…”
Section: Discussionsupporting
confidence: 42%
“…In accordance with this fact, emerging clinical data suggest that MSI-H CRC patients may obtain more benefit from CPT-11-based chemotherapy than patients bearing MSS tumours (Fallik et al, 2003;Bertagnolli et al, 2006). Still, preclinical evidence suggesting a higher sensitivity of MMR-deficient tumours to irinotecan (CPT-11) is controversial due to discrepant results coming from different studies (Hausner et al, 1999;Jacob et al, 2001;Magrini et al, 2002;Fedier and Fink, 2004).…”
supporting
confidence: 40%
See 1 more Smart Citation
“…It is recognised that defective DNA mismatch repair (MMR) leads to MSI and results in resistance to many antineoplastic drugs, such as antimetabolites, alkylating, and platinum agents, and inhibitors of topoisomerases. There are some evidences in vitro that suggest a correlation between response to 5-FU, OXA, and IRI and MSI (Magrini et al, 2002;Arnold et al, 2003;Warusavitarne and Schnitzler, 2007). Our analysis plan did not include an MSI analysis.…”
Section: Discussionmentioning
confidence: 40%
“…Interestingly, Magrini et al 42 showed that the absence of MLH1 protein actually enhances CPT-11-induced apoptosis, and that triggering of cell cycle arrest was p53 independent. Thus, a theoretical basis was formed for the development of chemotherapeutic strategies specifically targeted to MSI þ cells.…”
Section: Chemotherapy Concernsmentioning
confidence: 42%